Edmund Dulac's Picture-book for the French Red Cross - Dulac, Edmund 1882-1953 (Publ. for the Daily Telegraph by Hodder and Stovghton, 1915)
The story of the bird Feng : a fairy tale from China -- Young Rousselle : a French song of the olden time -- Laylá and Majnún : a Persian love story -- The nightingale : after a fairy tale by Hans Andersen -- Three kings of orient : a carol -- Sindbad the sailor : a tale from the Thousand and one nights -- The little seamstress : a French song of the olden time -- The real princess : after a fairy tale by Hans Andersen -- My Lisette : an old French song -- Cinderella : a fairy tale from the French -- The chilly lover : a song from the French -- The story of Aucassin and Nicolette : an old world idyll -- Blue beard : an old tale from the French -- Cerberus, the black dog of Hades -- The Lady Badoura : a tale from the Thousand and one nights -- The sleeper awakened : a tale from the Thousand and one nights -- Jusef and Asenath : a love story of Egypt.